INVESTIGATING STUDENTS’ ONLINE LEARNING EXPERIENCE USING REVISED COMMUNITY OF INQUIRY FRAMEWORK IN AN EFL WRITING COURSE - Mega Wulandari (ELTR Journal, 2022)
Quality online programs often demonstrate significant teaching presence, social presence, cognitive presence, learner presence with the help of technology use. This study investigates online learning experience based on the Revised Community of Inquiry (RCoI) framework in a writing course. The goal of this study is to explore how asynchronous and synchronous activities in an LMS can be utilized to create higher levels of cognitive presence in the online environment. Learning experience of one writing course consisting 28 students were assessed through questionnaire & FGD. Hopefully, the result of this study will contribute to the more accessible, convenient, and effective online learning in the future.